Evaluation of Whole Transcriptome Amplification Methods by RNA-Seq - Vallandingham, Jim (Association of Biomolecular Resource Facilities, 2013)
Library construction for whole transcriptome sequencing (RNA-Seq) from low-quantity RNA samples requires additional amplification after reverse transcription into cDNA. Several approaches have been developed to minimize variability and biases. This study aimed at quantifying and characterizing transcripts amplified using four commercial kits: (1) NuGEN Ovation RNA-Seq System V2, (2) Clontech SMARTer Ultra Low RNA Kit for Illumina Sequencing, (3) Sigma Transplex WTA2-SEQ Kit and (4) Miltenyi Biotec μMACS SuperAmp Kit II for NGS. The amplification reactions for each method were started with input amounts of Universal Mouse Reference RNA (UMRR) equivalent to approximately 10 to 300 cells. Resulting libraries built according to Illumina's TruSeq procedure were compared to unamplified references prepared from 1 μg of UMR total RNA that was either enriched for poly-A RNA or depleted of rRNA. Sequencing data were evaluated for read alignment, library complexity, transcript coverage, and gene expression with regard to sensitivity and dynamic range. The Sigma kit-derived samples showed overrepresentation of genes categorized as snoRNAs, snRNAs and pseudogenes. The current Miltenyi Biotec protocol yielded low library complexity and increase of multi-mapped reads. Samples amplified with the Clontech and NuGEN methods performed well across all criteria. These kits will be tested further using cells as starting material.